CXCL17 binds efficaciously to glycosaminoglycans with the potential to modulate chemokine signaling - Giblin, Sean P.; Ranawana, Sashini; Hassibi, Shyreen; Birchenough, Holly L.; Mincham, Kyle T.; Snelgrove, Robert J.; Tsuchiya, Tomoko; Kanegasaki, Shiro; Dyer, Douglas; Pease, James E. (Frontiers in Immunology, 2023)
CXCL17 is a mucosally secreted protein, and the most recently identified human chemokine, an assignment based on protein fold prediction and chemotactic activity for leukocytes. However, these credentials have been the subject of much recent discussion and no experimental evidence has been presented regarding the definitive structure of CXCL17. In this study, we evaluated the structural and chemoattractant credentials of CXCL17 to better characterise this molecule, and gain deeper insights into its functional role as a glycosaminoglycan (GAG) binding protein. In the absence of structural information, in silico modelling techniques assessed the likelihood of CXCL17 adopting a chemokine-fold. Recombinant CXCL17 was synthesized in mammalian and prokaryotic systems. Modified Boyden chamber and real-time chemotaxis assays assessed the ability of CXCL17 to promote chemotaxis of murine splenocytes, human neutrophils and CXCR1-transfectants. The efficacy of CXCL17 binding to GAGs was quantified with solid-phase assays and bio-layer interferometry techniques. All modelling efforts failed to support classification of CXCL17 as a chemokine based on its predicted conformation. Recombinant CXCL17 was observed to dimerize as a function of concentration, a characteristic of several chemokines. Contrary to a previous report, CXCL17 was not chemotactic for murine splenocytes, although it was a low-potency chemoattractant for human neutrophils at micromolar concentrations, several orders of magnitude higher than those required for CXCL8. As anticipated due to its highly basic nature, CXCL17 bound to GAGs robustly, with key C-terminal motifs implicated in this process. While inactive via CXCR1, CXCL17 was found to inhibit CXCR1-mediated chemotaxis of transfectants to CXCL8 in a dose-dependent manner. In summary, despite finding little evidence for chemokine-like structure and function, CXCL17 readily bound GAGs, and could modulate chemotactic responses to another chemokine in vitro. We postulate that such modulation is a consequence of superior GAG-binding, and that C-terminal fragments of CXCL17 may serve as prototypic inhibitors of chemokine function.